Stress‐related growth following sport injury: Examining the applicability of the organismic valuing theory. Issue 10 (21st November 2015) - Wadey, R.; Podlog, L.; Galli, N.; Mellalieu, S. D.
Abstract : This study explored the applicability of organismic valuing theory (OVT) to stress‐related growth (SRG) following sport injury. Specifically, the direct and indirect relationships between need satisfaction (i.e., autonomy, competence, and relatedness), SRG, and subjective well‐being (i.e., positive affect) were examined. Previously injured athletes ( n  = 520), ranging from 18 to 59 years of age (Mage  = 23.3 years; standard deviation = 6.5), completed three measures: needs satisfaction scale, stress‐related growth scale, and positive affect scale. Structural equation modeling with maximum likelihood estimation revealed a significant positive relationship between competence and relatedness and SRG, and between SRG and positive affect. In line with OVT, SRG was also found to mediate the relationship between need satisfaction (competence and relatedness) and subjective well‐being. The findings offer preliminary support for the applicability of OVT in aiding our understanding of the antecedents and consequences of SRG. Future avenues of research are discussed, together with recommended methodologies to further extend and refine knowledge and understanding of the phenomenon of SRG following sport injury.